2021
DOI: 10.3389/fped.2021.713588
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics Modeling of Vancomycin Among Chinese Infants With Normal and Augmented Renal Function

Abstract: There have been good amounts of population pharmacokinetics (PPK) models of vancomycin for Chinese pediatric patients, but none of them had a special focus on modeling infant population with different levels of renal function. Since renal function variability is prominent among infant population and the clearance (CL) of vancomycin is heavily related to renal excretion, it is important to establish precise PPK models based on individual renal function levels. We employed a PPK approach to develop three models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As illustrated in Figure 1 , an approximately linear correlation was only observed between vancomycin CL and eGFR below 120 mL/min/1.73 m 2 . This finding is in agreement with previous studies by Smit et al ., 27 Li et al ., 12 Lv et al . 36 and Yamamoto et al ., 37 who also reported that vancomycin CL was correlated with eGFR only in patients with normal or impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure 1 , an approximately linear correlation was only observed between vancomycin CL and eGFR below 120 mL/min/1.73 m 2 . This finding is in agreement with previous studies by Smit et al ., 27 Li et al ., 12 Lv et al . 36 and Yamamoto et al ., 37 who also reported that vancomycin CL was correlated with eGFR only in patients with normal or impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that WT and age are the critical variables that must be considered when establishing vancomycin PPK models for children, particularly for young infants. 12 Therefore, we evaluated these two covariates at first in a series of size and maturation models. 17 , 18 The maturation factor (MF), was used to describe the developmental contribution to CL.…”
Section: Methodsmentioning
confidence: 99%